2015
DOI: 10.3945/an.114.007575
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Selenium in Adjuvant Therapy of Viral and Bacterial Infections

Abstract: Viral and bacterial infections are often associated with deficiencies in macronutrients and micronutrients, including the essential trace element selenium. In selenium deficiency, benign strains of Coxsackie and influenza viruses can mutate to highly pathogenic strains. Dietary supplementation to provide adequate or supranutritional selenium supply has been proposed to confer health benefits for patients suffering from some viral diseases, most notably with respect to HIV and influenza A virus (IAV) infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
215
0
23

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 259 publications
(246 citation statements)
references
References 93 publications
8
215
0
23
Order By: Relevance
“…Dietary supplementation containing selenium supply has been proposed to confer health benefits by improving the immune response to viral infections, especially with respect to influenza A virus, and response to influenza vaccine. [64][65][66] A study in Japan investigated the favorable effects Mekabu fucoidan, a sulfated polysaccharide extracted from seaweed, concerning the immune response to influenza vaccine. The study revealed that Mekabu fucoidan intake increased antibody production after vaccination, perhaps preventing influenza epidemics.…”
Section: Dietary Supplementsmentioning
confidence: 99%
“…Dietary supplementation containing selenium supply has been proposed to confer health benefits by improving the immune response to viral infections, especially with respect to influenza A virus, and response to influenza vaccine. [64][65][66] A study in Japan investigated the favorable effects Mekabu fucoidan, a sulfated polysaccharide extracted from seaweed, concerning the immune response to influenza vaccine. The study revealed that Mekabu fucoidan intake increased antibody production after vaccination, perhaps preventing influenza epidemics.…”
Section: Dietary Supplementsmentioning
confidence: 99%
“…In addition, viral reassortment and cross-infection play a contributory role in the ineffectiveness of the vaccine. In particular, previous studies have provided evidence that the severity of viral infection is associated with some environmental, nutritional, and immune factors, such as mycotoxin contamination [3,4], selenium deficiency [5,6], and macrophage polarization [7]. These factors may partially explain the global differences in morbidity and mortality in animals and humans.…”
Section: Introductionmentioning
confidence: 99%
“…Se status affects functions of both innate and adaptive immune cells; deficiency of Se can cause decreased lymphocyte proliferation or decreased immunoglobulin concentrations . When supplemented supranutritionally, Se favors increased proliferation and differentiation of naive CD4 + T‐lymphocytes into Th1 cells, resulting in stimulation of acute cellular immune responses . Liu et al found that selenylation of Atractylodes macrocephala polysaccharide with sodium selenite increased the immune‐enhancing ability of that polysaccharide when injected into chickens vaccinated with ND vaccine .…”
Section: Discussionmentioning
confidence: 99%